Properties and Characteristics of Regolith-Based Materials for Extraterrestrial Construction - Cheng Zhou; Yuyue Gao; Yan Zhou; Wei She; Yusheng Shi; Lieyun Ding; Changwen Miao (Engineering, 2024)
The construction of extraterrestrial bases has become a new goal in the active exploration of deep space. Among the construction techniques, in situ resource-based construction is one of the most promising because of its good sustainability and acceptable economic cost, triggering the development of various types of extraterrestrial construction materials. A comprehensive survey and comparison of materials from the perspective of performance was conducted to provide suggestions for material selection and optimization. Thirteen types of typical construction materials are discussed in terms of their reliability and applicability in extreme extraterrestrial environment. Mechanical, thermal and optical, and radiation-shielding properties are considered. The influencing factors and optimization methods for these properties are analyzed. From the perspective of material properties, the existing challenges lie in the comprehensive, long-term, and real characterization of regolith-based construction materials. Correspondingly, the suggested future directions include the application of high-throughput characterization methods, accelerated durability tests, and conducting extraterrestrial experiments.